Perlindungan Hukum bagi Lanjut Usia Terlantar - Lestari, Gita Ayu (Jurnal El-Thawalib, 2021)
The problem in this research is the extent to which the implementation of Law Number 11 Year 2009 Article 9 concerning Social Welfare Against Legal Protection for Abandoned Elderly in Public Services at the Titian Ridho Divine Nursing Home, Huta Holbung Village, Batang Angkola District, South Tapanuli Regency because of the process of organizing social welfare in protection. and the services provided by the Titian Ridho Divine Nursing Home Al Yusufiyah Foundation are not in accordance with Article 9 of Law Number 11 of 2009 concerning Social Welfare. The needs given to the elderly are not in accordance with those stipulated in Law Number 11 of 2009 namely the need for food and clothing, the need for peace, social needs and self-actualization needs. The purpose of this study is to describe and analyze the implementation of Law Number 11 of 2009 Article 9 concerning Social Welfare for Legal Protection for Abandoned Elderly in Public Services at the Titian Ridho Divine Nursing Home Al Yusufiyah Foundation, Huta Holbung Village, Batang Angkola District, South Tapanuli Regency. The formulation of the research problem is how to implement Law Number 11 of 2009 Article 9 concerning Social Welfare towards Legal Protection for Abandoned Elderly in Public Services at the Titian Ridho Divine Nursing Home, Al Yusufiyah Foundation, Huta Holbung Village, Batang Angkola District, South Tapanuli Regency and what are the factors? which affects the implementation of Law Number 11 of 2009 concerning Social Welfare at the Titian Ridho Divine Nursing Home Al Yusufiyah Foundation. The research method used in this study is a qualitative approach using descriptive methods, which describe phenomena that occur in the field. The data collection instruments used in this study consisted of interviews, observations, and documentation. The result of this research is the implementation of Law Number 11 Year 2009 Article 9 concerning Social Welfare Against Legal Protection for Abandoned Elderly in Public Services at the Titian Ridho Divine Nursing Home, Huta Holbung Village, Batang Angkola District, South Tapanuli Regency. The caretaker of the Titian Ridho Divine Nursing Home Al Yusufiyah Foundation is lacking in meeting the needs given because the orphanage only provides cottages and the activities provided are only recitation activities.